Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

The Queensland Bloodstream Infections (QBSI) study: rationale, protocol development and future directions - Kevin B. Laupland; Felicity Edwards; Patrick N. A. Harris; Adam Irwin; Burcu Isler; Holly Hamilton; Sonali Coulter; Adam G. Stewart (Infectious Diseases, 2026)

Adverse childhood experiences, adult adiposity, and risk of young-onset breast cancer subtypes in a population-based case-control study - Lydia Marcus Post; Young Ik Cho; James Topitzes; DPhuong Do; Dorothy R. Pathak; Ann S. Hamilton; Amani M. Nuru-Jeter; Kelly A. Hirko; Jamila L. Kwarteng; Richard Houang; Ann G. Schwartz; Ellen M. Velie (Cancer Causes & Control, 2026)
Purpose Adverse childhood experiences (ACEs) are hypothesized to increase breast cancer risk via social and physiological pathways, yet associations between ACEs and young-onset breast cancer (BC) subtypes–and potential mediators (e.g., adiposity) of these associations–are largely unstudied. We sought to evaluate associations between ACEs and young-onset BC molecular subtypes, and the potential mediating effects of adiposity, in a population-based case–control study of invasive young-onset BC. Methods Cases (n = 1,754) were identified from the Los Angeles County and Metropolitan Detroit SEER registries, 2010–2015, and area-based, frequency-matched controls (n = 1,350) sampled from the 2010 Census. Associations between ACEs aged < 18 years and young-onset BC (diagnosed ages 20 to < 50 years), overall and by subtype (luminal A, luminal B, HER2 + , triple negative [TN]), were examined using weighted logistic regression. Adult adiposity (i.e., body mass index 12 months before diagnosis, waist circumference at interview) was evaluated as a mediator of these associations using weighted path analyses. Results ACEs (≥ 1 vs 0) were not significantly associated with young-onset BC (all p trend > 0.10); however, reporting one ACE (vs 0) was associated with TN (odds ratio [OR] = 1.85 [95% confidence interval [95%CI] = 1.08–3.16]). For individual ACEs, death of a loved one (vs 0 ACEs) was associated with HER2 + (OR = 2.50 [95%CI = 1.06–5.88]) and potentially TN (OR = 1.72 [95%CI = 0.96–3.10]) young-onset BC; other associations were non-significant. In path analyses, ACEs had a significant total effect on luminal A (β = 0.08, p = 0.03) and TN (β = 0.13, p < 0.01) tumors, with adiposity mitigating this association for luminal A tumors (β = -0.01, p = 0.04; TN β = 0.00, p > 0.05). Conclusions Bereavement during childhood was associated with higher odds of HER2 + young-onset BC, and there was some evidence of an association between ACEs and other young-onset BC subtypes, particularly TN.

Finding needles in a haystack: measuring ambient concentrations of naturally occurring elongated mineral particles in an urban environment - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Wenxia (Wendy) Fan; Araliya de Zoysa; Cindy Z. Yi; Paul G. Young; Ayrton Hamilton; Nick Talbot; Martin Brook; Brett Wells; David E. Williams; et al. (Chemosphere, 2026)

Drought and reservoir drawdown: implications for bull trout distribution and passage - Blake R. Hamilton; Connor D. Cunningham; Brittany A. Beebe; Craig A. Haskell; Jason G. Romine (Environmental Biology of Fishes, 2026)

Respirable mineral fibres in leaf surface dust: Micro-characterisation and evidence of a geogenic origin - Wenxia (Wendy) Fan; Kim N. Dirks; Alessandro F. Gualtieri; Paul G. Young; Ayrton Hamilton; Janki P. Patel; Timothy D. Christopher; Jennifer A. Salmond (Chemosphere, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Ocean circulation, sea ice, and productivity simulated in Jones Sound, Canadian Arctic Archipelago, between 2003–2016 - Tyler Pelle; Paul G. Myers; Andrew Hamilton; Matthew Mazloff; Krista M. Soderlund; Lucas Beem; Donald D. Blankenship; Cyril Grima; Feras Habbal; Mark Skidmore; Jamin S. Greenbaum (Ocean Science, 2026)
Jones Sound is one of three critical waterways in the Canadian Arctic Archipelago that regulate liquid exchange between the Arctic Ocean and northern Atlantic Ocean. However, to date, no high-resolution ocean circulation model exists to study the recent evolution of Jones Sound, meaning that our understanding of circulation within the sound is based either on temporally and spatially sparse oceanographic observations or on extrapolating conditions within Baffin Bay, which has a more dense observational record. To address this, we develop a high-resolution (1/120°, 0.9 km) Jones Sound configuration of the Massachusetts Institute of Technology general circulation model and perform coupled ocean–sea ice–biological productivity simulations between 2003–2016. We find that circulation through Lady Ann Strait, Fram Sound, and Glacier Strait comprises 71 %, 14 %, and 15 % of the volumetric transport into and out of Jones Sound, with tidal flushing enhancing the magnitude of volumetric transport through Fram Sound. Warming Atlantic Water within western Baffin Bay flows into Jones Sound through Lady Ann Strait, becomes well-mixed, and circulates counterclockwise, encroaching on the terminus of most tidewater glaciers that line the eastern periphery of the sound. Furthermore, we find that sustained atmospheric and oceanic warming drives an 11 % reduction in the 2003–2016 mean summertime sea ice area, decreased wintertime sea ice thickness, and delayed onset of sea ice refreeze in the fall (thus lengthening the amount of time during which Jones Sound is ice-free). Tidal flushing through Cardigan Strait is critical in triggering melt-back of sea ice across northern Jones Sound. Lastly, this decline in sea ice increases light availability and, when coupled with warming of the subsurface waters in Jones Sound, facilitates enhanced primary productivity down to ∼ 21 m depth. While we note that the modeled warming signal in Baffin Bay is overestimated relative to observations, the results presented here improve our general understanding of how this critical waterway might change under continued polar-amplified global warming and underscores the need for sustained oceanographic observations in this region.

Exploiting interspecific conservation of male-specific genomic regions to develop markers for sex determination in catla (Labeo catla) and silver carp (Hypophthalmichthys molitrix) - Matthew G. Hamilton; Md. Masud Akhter; Sirajum Monira Shanta; Aashish Kumar Roy; Md. Mustafizur Rahman; Uzzal Kumar Sarkar; Md. Kamruzzaman; John A.H. Benzie (Aquaculture, 2026)

A phenology-guided approach for detecting grassland invasive species using satellite image time series - Md Saiful Islam; Hamed Gholizadeh; M. Ny Aina Rakotoarivony; Robert G. Hamilton; Samuel Fuhlendorf; Yuting Zhou; Smriti Shrestha (Remote Sensing Applications: Society and Environment, 2026)

Characterization of a Peptidoglycan-Degrading Protein: Biochemical and Antimicrobial Characteristics, Antibiotic Synergism, and Delivery System Innovation - Viviane C. Oliveira; Nathália G. Rosa-Garzon; Amanda C.S.D. Rocha; Rachel M. Monteiro; Yasmim G. Gonçalves; Marcelo Kravicz; Maria A. Juliano; Luiz Juliano; Priscyla D. Marcato; Claudia H. Silva-Lovato; Hamilton Cabral; Evandro Watanabe (Probiotics and Antimicrobial Proteins, 2025)

Perturbation solution for second-harmonic generation in focused shear wave beams in soft solids - Philip G. Kaufinger; John M. Cormack; Kyle S. Spratt; Mark F. Hamilton (Wave Motion, 2025)

Evidence of airborne dispersion of respirable-sized carcinogenic erionite fibres of volcanic origin - Wenxia (Wendy) Fan; Kim N. Dirks; Alessandro F. Gualtieri; Paul G. Young; Ayrton Hamilton; Janki P. Patel; Jennifer A. Salmond (Environmental Research, 2025)

Neuromusculoskeletal Modeling and Force Prediction: Verification Through Experimental Neuromuscular Dynamics - Colton D. Babcock; Landon D. Hamilton; Anastasios Lykidis; Richard Babcock; Ioannis G. Amiridis; Clare K. Fitzpatrick (Annals of Biomedical Engineering, 2025)
Purpose Neuromusculoskeletal (NMS) function is influenced by the interactions between neural and musculoskeletal systems. Age-related changes in motor unit morphology contribute to changes in motor control and force production with advancing age; however, a better understanding of the underlying mechanisms between force production and motor unit reorganization and their interrelationships is needed to develop targeted therapies and interventions to age-related changes. Direct experimental measurement of these neuromuscular changes is challenging due to ethical and logistical constraints and the complexity of isolating individual motor unit contributions in vivo, particularly across time. Computational modeling provides a complementary approach which can help bridge this gap. The objective of this study is to develop a computational framework for predicting dorsiflexion force profiles through the translation of experimental motor unit recordings into simulated musculoskeletal responses. Methods This study presents the development of a combined NMS model that integrates experimental motor unit recordings into a musculoskeletal simulation framework. Specifically, the NMS model predicts dorsiflexion force profiles by translating experimental data from high-density electromyography recordings into simulated subject-specific motor unit discharge characteristics and simulated muscle responses. The NMS model incorporates a detailed motor neuron pool simulation and a finite element musculoskeletal model, allowing for physiologically accurate representation of motor unit discharge characteristics, muscle force generation, and force variability. Results The accuracy of the simulated force profiles in predicting the experimental force were 10.25 N and 0.95, respectively, for average root mean square error and R 2 values. Results demonstrate strong agreement between simulated and experimental force profiles and motor unit recordings. Conclusion By bridging the gap between computational and experimental approaches, this study aims to enhance understanding of NMS dynamics and support the development of personalized treatment strategies for neurodegenerative disease patients.

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Molecular modeling of a novel butane-substituted chalcone: from synthesis to comprehensive electron density analysis - Aécio V. B. Oliveira; Vitor S. Duarte; Renata Layse. G. de Paula; Jaqueline E. Queiroz; Gilberto L. B. de Aquino; Hamilton B. Napolitano; Ademir J. Camargo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Parental perspectives on the use of tumor molecular profiling and germline genetic testing during their children's cancer treatment - Marcelo M. Sleiman; Muriel R. Statman; Mary Rose Yockel; Yelena P. Wu; Jada G. Hamilton; Wendy K. Kohlmann; Jennie Vagher; Soren Feola; Luke D. Maese; Jing Chen; Burton Appel; Casey J. Mehrhoff; et al. (Familial Cancer, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Wave-influenced connectivity and transport in submerged coral canopies - J. F. Hamilton; S. G. Monismith; J. R. Koseff (Coral Reefs, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Is trauma associated with plant-based diet choice? - Faith O. Nomamiukor; Madeline A. Smethurst; Molly R. Franz; Evelyn G. Hamilton; Anissa Garza; Diana Padilla-Medina; Maxine Davis; Casey T. Taft (Appetite, 2025)

Evaluating the influence of marine protected areas on surf zone fish - M. L. Marraffini; S. L. Hamilton; J. R. Marin Jarrin; M. Ladd; G. Koval; J. R. Madden; I. Mangino; L. M. Parker; K. A. Emery; K. Terhaar; D. M. Hubbard; R. J. Miller; et al. (Conservation Biology, 2024)
Marine protected areas (MPAs) globally serve conservation and fisheries management goals, generating positive effects in some marine ecosystems. Surf zones and sandy beaches, critical ecotones bridging land and sea, play a pivotal role in the life cycles of numerous fish species and serve as prime areas for subsistence and recreational fishing. Despite their significance, these areas remain understudied when evaluating the effects of MPAs. We compared surf zone fish assemblages inside and outside MPAs across 3 bioregions in California (USA). Using seines and baited remote underwater videos (BRUVs), we found differences in surf zone fish inside and outside MPAs in one region. Inside south region MPAs, we observed higher abundance (Tukey's honest significant difference [HSD] = 0.83, p = 0.0001) and richness (HSD = 0.22, p = 0.0001) in BRUVs and greater biomass (HSD = 0.32, p = 0.0002) in seine surveys compared with reference sites. Selected live‐bearing, fished taxa were positively affected by MPAs. Elasmobranchs displayed greater abundance in BRUV surveys and higher biomass in seine surveys inside south region MPAs (HSD = 0.35, p = 0.0003 and HSD = 0.23, p = 0.008, respectively). Although we observed no overall MPA signal for Embiotocidae, abundances of juvenile and large adult barred surfperch ( Amphistichus argenteus ), the most abundant fished species, were higher inside MPAs (K–S test D = 0.19, p

Estimating plant β-diversity using airborne and spaceborne imaging spectroscopy - Nivedita Priyadarshini Kamaraj; Hamed Gholizadeh; Robert G. Hamilton; Samuel D. Fuhlendorf; John A. Gamon (International Journal of Remote Sensing, 2024)

Environmental analogs from yellowstone hot springs on geochemical and microbial diversity with implications for the search for life on Mars - D. Boulesteix; A. Buch; G. Masson; L.L. Kivrak; J.R. Havig; T.L. Hamilton; B.L. Teece; Y. He; C. Freissinet; Y. Huang; E. Santos; C. Szopa; et al. (Planetary and Space Science, 2024)

How water stability relates with timing, size, and community successions of harmful algal blooms: A case study in the Three Gorges Reservoir - Xuexing Yao; Zenghui Song; Guanglang Yang; Muhammad Waqas Yonas; Paul B. Hamilton; Amechi S. Nwankwegu; Oluwafemi Adeyeye; Wei Huang; Xiaojiao Luo; Abdelrahman M. Hassaan; G. Douglas Haffner; Lei Zhang (Marine Pollution Bulletin, 2024)

Does salinity mediate the toxicity of perfluorooctanesulfonic acid (PFOS) in an estuarine fish? - Lucy E. Burcham; Tyler D. Hoskins; Elizabeth B. Allmon; Meredith N. Scherer; Anna G. Bushong; Matthew T. Hamilton; Sini Macheri; Grace S. Coogan; Youn J. Choi; Linda S. Lee; Maria S. Sepúlveda (Marine Pollution Bulletin, 2024)

Detection of viable Toxoplasma gondii in retail venison - J. Thomson; M. Joeres; G. Schares; E.A. Innes; C.M. Hamilton (Food Control, 2024)

Advancing our understanding of plant diversity-biological invasion relationships using imaging spectroscopy - Hamed Gholizadeh; M. Ny Aina Rakotoarivony; Kianoosh Hassani; Kayla G. Johnson; Robert G. Hamilton; Samuel D. Fuhlendorf; Fabian D. Schneider; Benedicte Bachelot (Remote Sensing of Environment, 2024)

Human habitat modification, not apex scavenger decline, drives isotopic niche variation in a carnivore community - Olivia Bell; Menna E. Jones; Manuel Ruiz-Aravena; David G. Hamilton; Sebastien Comte; Rowena Hamer; Rodrigo K. Hamede; Jason Newton; Stuart Bearhop; Robbie A. McDonald (Oecologia, 2024)
Top carnivores can influence the structure of ecological communities, primarily through competition and predation; however, communities are also influenced by bottom-up forces such as anthropogenic habitat disturbance. Top carnivore declines will likely alter competitive dynamics within and amongst sympatric carnivore species. Increasing intraspecific competition is generally predicted to drive niche expansion and/or individual specialisation, while interspecific competition tends to constrain niches. Using stable isotope analysis of whiskers, we studied the effects of Tasmanian devil Sarcophilus harrisii declines upon the population- and individual-level isotopic niches of Tasmanian devils and sympatric spotted-tailed quolls Dasyurus maculatus subsp. maculatus. We investigated whether time since the onset of devil decline (a proxy for severity of decline) and landscape characteristics affected the isotopic niche breadth and overlap of devil and quoll populations. We quantified individual isotopic niche breadth for a subset of Tasmanian devils and spotted-tailed quolls and assessed whether between-site population niche variation was driven by individual-level specialisation. Tasmanian devils and spotted-tailed quolls demonstrated smaller population-level isotopic niche breadths with increasing human-modified habitat, while time since the onset of devil decline had no effect on population-level niche breadth or interspecific niche overlap. Individual isotopic niche breadths of Tasmanian devils and spotted-tailed quolls were narrower in human-modified landscapes, likely driving population isotopic niche contraction, however, the degree of individuals’ specialisation relative to one another remained constant. Our results suggest that across varied landscapes, mammalian carnivore niches can be more sensitive to the bottom-up forces of anthropogenic habitat disturbance than to the top-down effects of top carnivore decline.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Decentralised solar-based water treatment – Bridging the last mile to water security in low- and middle-income countries? - Brandon Reyneke; Tinta C. Morris; Pilar Fernández-Ibáñez; Kevin G. McGuigan; Ashley Heida; Kerry A. Hamilton; Wesaal Khan (Water Security, 2023)

Cold tolerance of Acanthoscelides obtectus, the bean weevil: Effects of cold acclimation, life stage and strain - Vincent A.D. Hervet; Paul G. Fields; Kimberly D. Hamilton; Mohammad Nadimi; Jitendra Paliwal (Journal of Stored Products Research, 2023)

Detecting the invasive Lespedeza cuneata in grasslands using commercial small satellite imagery - M. Ny Aina Rakotoarivony; Hamed Gholizadeh; William M. Hammond; Kianoosh Hassani; Omkar Joshi; Robert G. Hamilton; Samuel D. Fuhlendorf; Amy M. Trowbridge; Henry D. Adams (International Journal of Remote Sensing, 2023)

Assessment of rapid wastewater surveillance for determination of communicable disease spread in municipalities - Mohsen Asadi; Daniel Hamilton; Corwyn Shomachuk; Femi F. Oloye; Chantel De Lange; Xia Pu; Charles A. Osunla; Jenna Cantin; Seba El-Baroudy; Edgard M. Mejia; Branden Gregorchuk; Michael G. Becker; et al. (Science of The Total Environment, 2023)

Metagenomic analysis of ethylene glycol contamination in anaerobic digestion - Gabrielle R. Joslin; Daniel G. Barber; Lindsay Aston; Ping Liu; Olukayode Kuloyo; Kangsa Oentoro; Jiayi Liu; Ashley V. Baugh; Jeffrey R. Fedenko; Ioannis Melas; Phillip G. Hamilton; Damian J. Allen; et al. (Bioresource Technology, 2023)

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

Increasing Skin Cancer Prevention in Young Adults: the Cumulative Impact of Personalized UV Photography and MC1R Genetic Testing - Yelena P. Wu; Jada G. Hamilton; Kimberly A. Kaphingst; Jakob D. Jensen; Wendy Kohlmann; Bridget G. Parsons; Helen M. Lillie; Xuechen Wang; Benjamin Haaland; Ali P. Wankier; Douglas Grossman; Jennifer L. Hay (Journal of Cancer Education, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Uptake and incorporation of Al, Cr, V, Zn and Mo in hematite: Competition, synergies and influence on structural properties - G. Scullett-Dean; J.L. Hamilton; O. Repina; H.E.A. Brand; E.D. Burton; M. Saunders; T.C. Santini (Journal of Hazardous Materials, 2023)

Genetic correlations between harvest weight and secondary traits in a silver carp (Hypophthalmichthys molitrix) genetic improvement program - Matthew G. Hamilton; Mohammed Yeasin; Vishnumurthy Mohan Chadag; Jérôme Delamare-Deboutteville; Partho Pratim Debnath; John A. H. Benzie (Aquaculture International, 2023)
In 2017, the base population of a family-based silver carp ( Hypophthalmichthys molitrix ) genetic improvement program was spawned in Bangladesh. This program aims to improve the growth rate of silver carp under polyculture production systems, through direct selection on the primary trait of harvest-age weight. The objective of this study was to quantify genetic variation in, and genetic correlations between, harvest-age weight (assessed on 8012 fish from 184 families) and a set of secondary traits (assessed on 1603 fish from 175 families). Secondary traits examined included feeding and digestive system traits (i.e. gill raker sponginess and gut length as a ratio of standard length), a morphometric trait (i.e. extent of overlap of pectoral and pelvic fins) and health traits (i.e. presence of Lernaea and prevalence of red spots — sites of inflammation/haemorrhaging). Despite not being under direct selection, genetic change in secondary traits is possible across generations in closed genetic improvement populations as a result of a correlated response to selection for the primary trait (i.e. indirect selection), adaptation to culture conditions, inbreeding and/or genetic drift. It was found that the additive genetic variance within genetic groups was significantly different from zero for all but the studied health traits. Heritability estimates for harvest-age weight and pectoral/pelvic fin overlap were moderate (0.24 and 0.22, respectively) but were low for gill raker score and relative gut length (0.12 and 0.09, respectively). Genetic correlations between harvest-age weight and secondary traits were not significantly different from zero, indicating that selection for harvest-age weight will not result in a correlated response to selection in the studied secondary traits.

Genotype-by-culture-system interaction in catla and silver carp: Monoculture and biculture - Matthew G. Hamilton; Wagdy Mekkawy; Md. Badrul Alam; Benoy K. Barman; Manjurul Karim; John A.H. Benzie (Aquaculture, 2023)

Quantification and uncertainty of root growth stimulation by elevated CO2 in a mature temperate deciduous forest - Clare Ziegler; Aleksandra Kulawska; Angeliki Kourmouli; Liz Hamilton; Zongbo Shi; A. Rob MacKenzie; Rosemary J. Dyson; Iain G. Johnston (Science of The Total Environment, 2023)

Land‐based climate solutions for the United States - G. Philip Robertson; Stephen K. Hamilton; Keith Paustian; Pete Smith (Global Change Biology, 2022)
Meeting end‐of‐century global warming targets requires aggressive action on multiple fronts. Recent reports note the futility of addressing mitigation goals without fully engaging the agricultural sector, yet no available assessments combine both nature‐based solutions (reforestation, grassland and wetland protection, and agricultural practice change) and cellulosic bioenergy for a single geographic region. Collectively, these solutions might offer a suite of climate, biodiversity, and other benefits greater than either alone. Nature‐based solutions are largely constrained by the duration of carbon accrual in soils and forest biomass; each of these carbon pools will eventually saturate. Bioenergy solutions can last indefinitely but carry significant environmental risk if carelessly deployed. We detail a simplified scenario for the United States that illustrates the benefits of combining approaches. We assign a portion of non‐forested former cropland to bioenergy sufficient to meet projected mid‐century transportation needs, with the remainder assigned to nature‐based solutions such as reforestation. Bottom‐up mitigation potentials for the aggregate contributions of crop, grazing, forest, and bioenergy lands are assessed by including in a Monte Carlo model conservative ranges for cost‐effective local mitigation capacities, together with ranges for (a) areal extents that avoid double counting and include realistic adoption rates and (b) the projected duration of different carbon sinks. The projected duration illustrates the net effect of eventually saturating soil carbon pools in the case of most strategies, and additionally saturating biomass carbon pools in the case of forest management. Results show a conservative end‐of‐century mitigation capacity of 110 (57–178) Gt CO 2 e for the U.S., ~50% higher than existing estimates that prioritize nature‐based or bioenergy solutions separately. Further research is needed to shrink uncertainties, but there is sufficient confidence in the general magnitude and direction of a combined approach to plan for deployment now.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Spatial Distribution of Heavy Metals in Near-Shore Marine Sediments of the Jeddah, Saudi Arabia Region: Enrichment and Associated Risk Indices - Riyadh F. Halawani; Myra E. Wilson; Kenneth M. Hamilton; Fahed A. Aloufi; Md. Abu Taleb; Aaid G. Al-Zubieri; Andrew N. Quicksall (Journal of Marine Science and Engineering, 2022)
Red Sea coastal development has rapidly accelerated in recent decades that has led to a rise in the anthropogenic heavy metal levels in sediments. A total of 80 surficial sediment samples were collected from the shallow waters along the eastern Red Sea coast near Jeddah, Saudi Arabia. These samples were collected from three locations, designated as North, Middle and South of Jeddah, to assess the concentrations of six heavy metals: chromium (Cr), manganese (Mn), nickel (Ni), copper (Cu), zinc (Zn), and lead (Pb). The results showed that the concentrations (mg/kg) of these metals in the studied sediments follow this order: Pb (77.34 ± 150.59) > Mn (36.52 ± 37.72) > Zn (18.02 ± 23.94) > Cr (9.56 ± 5.81) > Cu (9.18 ± 13.67) > Ni (3.68 ± 4.54). The majority of the polluted sediments were recorded in the Middle and South locations. Pollution and enrichment indices such as Geo-accumulation indices (Igeo), Enrichment Factors (Ef), Contamination Factors (Cf), Pollution Load Indices (PLI), Potential Ecological Risk Indices (PERI) and Potential Toxicity Response Indices (RI) were calculated from the measured metals to establish baselines for the region and assess specific metal enrichments by location along the Jeddah coastline. The Igeo values showed that 30% of the Southern location stations are considered moderately to highly polluted. The Ef for all the studied sediments followed this order: Pb (extremely severe enrichment) > Zn > Cu > Cd > Cr (severe enrichment) > Ni (moderate enrichment).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Global co‐occurrence of methanogenic archaea and methanotrophic bacteria in Microcystis aggregates - Chuang Li; K. David Hambright; Hannah G. Bowen; Majoi A. Trammell; Hans‐Peter Grossart; Michele A. Burford; David P. Hamilton; Helong Jiang; Delphine Latour; Elisabeth I. Meyer; Judit Padisák; Richard M. Zamor; et al. (Environmental Microbiology, 2021)
Summary Global warming and eutrophication contribute to the worldwide increase in cyanobacterial blooms, and the level of cyanobacterial biomass is strongly associated with rises in methane emissions from surface lake waters. Hence, methane‐metabolizing microorganisms may be important for modulating carbon flow in cyanobacterial blooms. Here, we surveyed methanogenic and methanotrophic communities associated with floating Microcystis aggregates in 10 lakes spanning four continents, through sequencing of 16S rRNA and functional marker genes. Methanogenic archaea (mainly Methanoregula and Methanosaeta ) were detectable in 5 of the 10 lakes and constituted the majority (~50%–90%) of the archaeal community in these lakes. Three of the 10 lakes contained relatively more abundant methanotrophs than the other seven lakes, with the methanotrophic genera Methyloparacoccus , Crenothrix , and an uncultured species related to Methylobacter dominating and nearly exclusively found in each of those three lakes. These three are among the five lakes in which methanogens were observed. Operational taxonomic unit (OTU) richness and abundance of methanotrophs were strongly positively correlated with those of methanogens, suggesting that their activities may be coupled. These Microcystis ‐aggregate‐associated methanotrophs may be responsible for a hitherto overlooked sink for methane in surface freshwaters, and their co‐occurrence with methanogens sheds light on the methane cycle in cyanobacterial aggregates.

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Seasonal environmental variability drives microdiversity within a coastal Synechococcus population - Kristen R. Hunter‐Cevera; Bryan R. Hamilton; Michael G. Neubert; Heidi M. Sosik (Environmental Microbiology, 2021)
Summary Marine microbes often show a high degree of physiological or ecological diversity below the species level. This microdiversity raises questions about the processes that drive diversification and permit coexistence of diverse yet closely related marine microbes, especially given the theoretical efficiency of competitive exclusion. Here, we provide insight with an 8‐year time series of diversity within Synechococcus , a widespread and important marine picophytoplankter. The population of Synechococcus on the Northeast U.S. Shelf is comprised of six main types, each of which displays a distinct and consistent seasonal pattern. With compositional data analysis, we show that these patterns can be reproduced with a simple model that couples differential responses to temperature and light with the seasonal cycle of the physical environment. These observations support the hypothesis that temporal variability in environmental factors can maintain microdiversity in marine microbial populations. We also identify how seasonal diversity patterns directly determine overarching Synechococcus population abundance features.

Applying a values‐based decision process to facilitate comanagement of threatened species in Aotearoa New Zealand - Thalassa McMurdo Hamilton; Stefano Canessa; Katie Clark; Pani Gleeson; Fiona Mackenzie; Troy Makan; Gena Moses‐Te Kani; Shona Oliver; Kevin A. Parker; John G. Ewen (Conservation Biology, 2021)
Ko koe ki tēnā, ko ahau ki tēnai kīwai o te kete (you at that, and I at this handle of the basket). This Māori (New Zealanders of indigenous descent) saying conveys the principle of cooperation—we achieve more through working together, rather than separately. Despite decades of calls to rectify cultural imbalance in conservation, threatened species management still relies overwhelmingly on ideas from Western science and on top‐down implementation. Values‐based approaches to decision making can be used to integrate indigenous peoples’ values into species conservation in a more meaningful way. We used such a values‐based method, structured decision making, to develop comanagement of pekapeka ( Mystacina tuberculata ) (short‐tailed bat) and tara iti ( Sternula nereis davisae ) (Fairy Tern) between Māori and Pākehā (New Zealanders of European descent). We implemented this framework in a series of workshops in which facilitated discussions were used to gather expert knowledge to predict outcomes and make management recommendations. For both species, stakeholders clearly stated their values as fundamental objectives from the start, which allowed alternative strategies to be devised that naturally addressed their diverse values, including mātauranga Māori (Māori knowledge and perspectives). On this shared basis, all partners willingly engaged in the process, and decisions were largely agreed to by all. Most expectations of conflicts between values of Western science and Māori culture were unfounded. Where required, positive compromises were made by jointly developing alternative strategies. The values‐based process successfully taha wairua taha tangata (brought both worlds together to achieve the objective) through codeveloped recovery strategies. This approach challenges the traditional model of scientists first preparing management plans focused on biological objectives, then consulting indigenous groups for approval. We recommend values‐based approaches, such as structured decision making, as powerful methods for development of comanagement conservation plans between different peoples.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Examination of FERMT1 expression in placental chorionic villi and its role in HTR8-SVneo cell invasion - E. Kawamura; G. B. Hamilton; E. I. Miskiewicz; D. J. MacPhee (Histochemistry and Cell Biology, 2021)

Corrigendum to: The global Microcystis interactome - K.V. Cook; C. Li; H. Cai; L.R. Krumholz; K.D. Hambright; H.W. Paerl; M.M. Steffen; A.E. Wilson; M.A. Burford; H.‐P. Grossart; D. P. Hamilton; H. Jiang; et al. (Limnology and Oceanography, 2021)

Quantifying 25 years of disease‐caused declines in Tasmanian devil populations: host density drives spatial pathogen spread - Calum X. Cunningham; Sebastien Comte; Hamish McCallum; David G. Hamilton; Rodrigo Hamede; Andrew Storfer; Tracey Hollings; Manuel Ruiz‐Aravena; Douglas H. Kerlin; Barry W. Brook; Greg Hocking; Manna E. Jones (Ecology Letters, 2021)
Infectious diseases are strong drivers of wildlife population dynamics, however, empirical analyses from the early stages of pathogen emergence are rare. Tasmanian devil facial tumour disease (DFTD), discovered in 1996, provides the opportunity to study an epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. We estimate the wild devil population peaked at 53 000 in 1996, less than half of previous estimates. DFTD spread rapidly through high‐density areas, with spread velocity slowing in areas of low host densities. By 2020, DFTD occupied >90% of the species' range, causing 82% declines in local densities and reducing the total population to 16 900. Encouragingly, our model forecasts the population decline should level‐off within the next decade, supporting conservation management focused on facilitating evolution of resistance and tolerance.

Talin-dependent integrin activation is required for endothelial proliferation and postnatal angiogenesis - Fadi E. Pulous; Jamie C. Carnevale; Zaki Al-Yafeai; Brenna H. Pearson; Jamie A. G. Hamilton; Curtis J. Henry; A. Wayne Orr; Brian G. Petrich (Angiogenesis, 2021)

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Comparative landscape genetics reveals differential effects of environment on host and pathogen genetic structure in Tasmanian devils ( Sarcophilus harrisii ) and their transmissible tumour - Christopher P. Kozakiewicz; Lauren Ricci; Austin H. Patton; Amanda R. Stahlke; Sarah A. Hendricks; Mark J. Margres; Manuel Ruiz‐Aravena; David G. Hamilton; Rodrigo Hamede; Hamish McCallum; Menna E. Jones; Paul A. Hohenlohe; et al. (Molecular Ecology, 2020)
Genetic structure in host species is often used to predict disease spread. However, host and pathogen genetic variation may be incongruent. Understanding landscape factors that have either concordant or divergent influence on host and pathogen genetic structure is crucial for wildlife disease management. Devil facial tumour disease (DFTD) was first observed in 1996 and has spread throughout almost the entire Tasmanian devil geographic range, causing dramatic population declines. Whereas DFTD is predominantly spread via biting among adults, devils typically disperse as juveniles, which experience low DFTD prevalence. Thus, we predicted little association between devil and tumour population structure and that environmental factors influencing gene flow differ between devils and tumours. We employed a comparative landscape genetics framework to test the influence of environmental factors on patterns of isolation by resistance (IBR) and isolation by environment (IBE) in devils and DFTD. Although we found evidence for broad‐scale costructuring between devils and tumours, we found no relationship between host and tumour individual genetic distances. Further, the factors driving the spatial distribution of genetic variation differed for each. Devils exhibited a strong IBR pattern driven by major roads, with no evidence of IBE. By contrast, tumours showed little evidence for IBR and a weak IBE pattern with respect to elevation in one of two tumour clusters we identify herein. Our results warrant caution when inferring pathogen spread using host population genetic structure and suggest that reliance on environmental barriers to host connectivity may be ineffective for managing the spread of wildlife diseases. Our findings demonstrate the utility of comparative landscape genetics for identifying differential factors driving host dispersal and pathogen transmission.

Effects of hypoxia on the behavior and physiology of kelp forest fishes - Evan G. Mattiasen; Neosha S Kashef; David M. Stafford; Cheryl A. Logan; Susan M. Sogard; Eric P. Bjorkstedt; Scott L. Hamilton (Global Change Biology, 2020)
Forecasts from climate models and oceanographic observations indicate increasing deoxygenation in the global oceans and an elevated frequency and intensity of hypoxic events in the coastal zone, which have the potential to affect marine biodiversity and fisheries. Exposure to low dissolved oxygen (DO) conditions may have deleterious effects on early life stages in fishes. This study aims to identify thresholds to hypoxia while testing behavioral and physiological responses of two congeneric species of kelp forest fish to four DO levels, ranging from normoxic to hypoxic (8.7, 6.0, 4.1, and 2.2 mg O 2 /L). Behavioral tests identified changes in exploratory behavior and turning bias (lateralization), whereas physiological tests focused on determining changes in hypoxia tolerance (pCrit), ventilation rates, and metabolic rates, with impacts on the resulting capacity for aerobic activity. Our findings indicated that copper rockfish ( Sebastes caurinus ) and blue rockfish ( Sebastes mystinus ) express sensitivity to hypoxia; however, the strength of the response differed between species. Copper rockfish exhibited reduced absolute lateralization and increased escape time at the lowest DO levels, whereas behavioral metrics for blue rockfish did not vary with oxygen level. Both species exhibited decreases in aerobic scope (as a function of reduced maximum metabolic rate) and increases in ventilation rates to compensate for decreasing oxygen levels. Blue rockfish had a lower pCrit and stronger acclimation response compared to copper rockfish. The differences expressed by each species suggest that acclimatization to changing ocean conditions may vary, even among related species that recruit to the same kelp forest habitat, leading to winners and losers under future ocean conditions. Exposure to hypoxia can decrease individual physiological fitness through metabolic and aerobic depression and changes to anti‐predator behavior, with implications for the outcome of ecological interactions and the management of fish stocks in the face of climate change.

Feral cat eradication on Dirk Hartog Island, Western Australia - D. Algar; M. Johnston; C. Tiller; M. Onus; J. Fletcher; G. Desmond; N. Hamilton; P. Speldewinde (Biological Invasions, 2020)

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Effect of Hydrologic, Geomorphic, and Vegetative Conditions on Avian Communities in The Middle Rio Grande of New Mexico - Sarah G. Hamilton; Sammy L. King; Gina Dello Russo; Michael D. Kaller (Wetlands, 2019)

Velocity Curvature Index: a Novel Diagnostic Biomarker for Large Vessel Occlusion - Samuel G. Thorpe; Corey M. Thibeault; Seth J. Wilk; Michael O’Brien; Nicolas Canac; Mina Ranjbaran; Christian Devlin; Thomas Devlin; Robert B. Hamilton (Translational Stroke Research, 2019)

Foraging consistency of coral reef fishes across environmental gradients in the central Pacific - Brian J. Zgliczynski; Gareth J. Williams; Scott L. Hamilton; Elisabeth G. Cordner; Michael D. Fox; Yoan Eynaud; Robert H. Michener; Les S. Kaufman; Stuart A. Sandin (Oecologia, 2019)

Algal scavenging of mercury in preindustrial Arctic lakes - P. M. Outridge; G. A. Stern; P. B. Hamilton; H. Sanei (Limnology and Oceanography, 2019)
The geochemical speciation of total mercury (THg) was examined in pre‐1800 Arctic lake sediments to improve understanding of the factors controlling “natural baseline” THg. Solid‐phase binding forms of THg were determined by sequential extraction of dated cores from three lakes in different ecozones (barren tundra, grassy tundra, and boreal forest). Sediment organic matter (OM) was mostly of algal origin. Mercury was highly concentrated in the sediment OM fraction (OM‐Hg), comprising 60–87% of THg, while OM (as total organic carbon) constituted only 0.6–13% of sediment dry weight (DW). OM‐Hg concentrations were equivalent to 159 ± 13 to 776 ± 215 ng Hg g −1 DW in algal OM and were enriched 2–39 times compared to sediment THg, indicating that even small changes in algal OM inputs could significantly alter THg. OM‐Hg explained 76–96% of the variation in THg concentrations over many centuries. Concentrations of S2 carbon (an algal productivity proxy) and OM‐Hg were significantly correlated in two lakes but not in the boreal forest lake possibly because of OM remineralization in its deep water column. Fluxes of S2 carbon, OM‐Hg, and THg were highly correlated in the barren tundra lake but could not be calculated for the other lakes. The results overall indicate that high algal Hg concentrations due to scavenging of available Hg controlled OM‐Hg flux to sediments, thus driving changes in THg concentrations and fluxes. These findings improve our understanding of the long‐term stability of baseline THg in northern lakes under a changing climate, including in the modern era.

Technical mitigation to reduce marine mammal bycatch and entanglement in commercial fishing gear: lessons learnt and future directions - Sheryl Hamilton; G. Barry Baker (Reviews in Fish Biology and Fisheries, 2019)

Complex interactions between climate change, sanitation, and groundwater quality: a case study from Ramotswa, Botswana - Bonnie M. McGill; Yvan Altchenko; Stephen K. Hamilton; Piet K. Kenabatho; Steven R. Sylvester; Karen G. Villholth (Hydrogeology Journal, 2019)

Characterization of Male-Produced Aggregation Pheromone of the Bean Flower Thrips Megalurothrips sjostedti (Thysanoptera: Thripidae) - Saliou Niassy; Amanuel Tamiru; James G. C. Hamilton; William D. J. Kirk; Roland Mumm; Cassie Sims; Willem Jan de Kogel; Sunday Ekesi; Nguya K. Maniania; Krishnakumari Bandi; Fraser Mitchell; Sevgan Subramanian (Journal of Chemical Ecology, 2019)

The greenhouse gas cost of agricultural intensification with groundwater irrigation in a Midwest U.S. row cropping system - Bonnie M. McGill; Stephen K. Hamilton; Neville Millar; G. Philip Robertson (Global Change Biology, 2018)
Groundwater irrigation of cropland is expanding worldwide with poorly known implications for climate change. This study compares experimental measurements of the net global warming impact of a rainfed versus a groundwater‐irrigated corn (maize)–soybean–wheat, no‐till cropping system in the Midwest US, the region that produces the majority of U.S. corn and soybean. Irrigation significantly increased soil organic carbon (C) storage in the upper 25 cm, but not by enough to make up for the CO 2 ‐equivalent (CO 2 e) costs of fossil fuel power, soil emissions of nitrous oxide (N 2 O), and degassing of supersaturated CO 2 and N 2 O from the groundwater. A rainfed reference system had a net mitigating effect of −13.9 (±31) g CO 2 e m −2 year −1 , but with irrigation at an average rate for the region, the irrigated system contributed to global warming with net greenhouse gas (GHG) emissions of 27.1 (±32) g CO 2 e m −2 year −1 . Compared to the rainfed system, the irrigated system had 45% more GHG emissions and 7% more C sequestration. The irrigation‐associated increase in soil N 2 O and fossil fuel emissions contributed 18% and 9%, respectively, to the system's total emissions in an average irrigation year. Groundwater degassing of CO 2 and N 2 O are missing components of previous assessments of the GHG cost of groundwater irrigation; together they were 4% of the irrigated system's total emissions. The irrigated system's net impact normalized by crop yield (GHG intensity) was +0.04 (±0.006) kg CO 2 e kg −1 yield, close to that of the rainfed system, which was −0.03 (±0.002) kg CO 2 e kg −1 yield. Thus, the increased crop yield resulting from irrigation can ameliorate overall GHG emissions if intensification by irrigation prevents land conversion emissions elsewhere, although the expansion of irrigation risks depletion of local water resources.

The effect of ammonia on canine polymorphonuclear cells - Craig R. Breheny; Richard J. Mellanby; Julie A. Hamilton; Adam G. Gow (Veterinary Research Communications, 2018)

Genetic structure and diversity of a rare woodland bat, Myotis bechsteinii: comparison of continental Europe and Britain - Patrick G. R. Wright; Patrick B. Hamilton; Henry Schofield; Anita Glover; Christopher Damant; Ian Davidson-Watts; Fiona Mathews (Conservation Genetics, 2018)

Computation of the inverse additive relationship matrix for autopolyploid and multiple-ploidy populations - Matthew G. Hamilton; Richard J. Kerr (Theoretical and Applied Genetics, 2018)

Perineuronal nets labeled by monoclonal antibody VC1.1 ensheath interneurons expressing parvalbumin and calbindin in the rat amygdala - Alexander J. McDonald; Patricia G. Hamilton; Colin J. Barnstable (Brain Structure and Function, 2018)

Sensor manufacturer, temperature, and cyanobacteria morphology affect phycocyanin fluorescence measurements - Caroline M. Hodges; Susanna A. Wood; Jonathan Puddick; Christopher G. McBride; David P. Hamilton (Environmental Science and Pollution Research, 2018)

Effects of Long-Term Anthropogenic Disturbance on the Benthic Episammic Diatom Community of an Ancient, Tropical Lake - Andrew J. Bramburger; Paul B. Hamilton; G. Douglas Haffner (Bulletin of Environmental Contamination and Toxicology, 2017)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

A Qualitative Exploration of Latinos’ Perceptions About Skin Cancer: the Role of Gender and Linguistic Acculturation - Vivian M. Rodríguez; Elyse Shuk; Guedy Arniella; C. Javier González; Francesca Gany; Jada G. Hamilton; Geoffrey S. Gold; Jennifer L. Hay (Journal of Cancer Education, 2017)

Moving higher and higher: imitators’ movements are sensitive to observed trajectories regardless of action rationality - Paul A. G. Forbes; Antonia F. de C. Hamilton (Experimental Brain Research, 2017)

Establishment and characterization of a platinum- and paclitaxel-resistant high grade serous ovarian carcinoma cell line - Pang-Ning Teng; Nicholas W. Bateman; Guisong Wang; Tracy Litzi; Brian E. Blanton; Brian L. Hood; Kelly A. Conrads; Wei Ao; Kate E. Oliver; Kathleen M. Darcy; William P. McGuire; Keren Paz; et al. (Human Cell, 2017)

Syrian hamster neuroplasticity mechanisms fail as temperature declines to 15 °C, but histaminergic neuromodulation persists - Jock S. Hamilton; Sat M. Chau; Kevin J. Malins; Giancarlo G. Ibanez; John M. Horowitz; Barbara A. Horwitz (Journal of Comparative Physiology B, 2017)

Short-Term Response of a Downstream Marine System to the Partial Opening of a Tidal-River Causeway - Travis G. Gerwing; Diana J. Hamilton; Myriam A. Barbeau; Katy Haralampides; Gordon Yamazaki (Estuaries and Coasts, 2017)

The effect of prior knowledge of test endpoint on non-local muscle fatigue - Alan R. Hamilton; David G. Behm (European Journal of Applied Physiology, 2017)

Disorder Amidst Membrane Order: Standardizing Laurdan Generalized Polarization and Membrane Fluidity Terms - Anthony G. Jay; James A. Hamilton (Journal of Fluorescence, 2017)

Do Men Receive Information Required for Shared Decision Making About PSA Testing? Results from a National Survey - Bryan Leyva; Alexander Persoskie; Allison Ottenbacher; Jada G. Hamilton; Jennifer D. Allen; Sarah C. Kobrin; Stephen H. Taplin (Journal of Cancer Education, 2016)

Variability in the chemistry of private drinking water supplies and the impact of domestic treatment systems on water quality - E. L. Ander; M. J. Watts; P. L. Smedley; E. M. Hamilton; R. Close; H. Crabbe; T. Fletcher; A. Rimell; M. Studden; G. Leonardi (Environmental Geochemistry and Health, 2016)

Tissue recovery practices and bioburden: a systematic review - S. Brubaker; K. Lotherington; Jie Zhao; B. Hamilton; G. Rockl; A. Duong; A. Garibaldi; N. Simunovic; D. Alsop; D. Dao; R. Bessemer; O. R. Ayeni (Cell and Tissue Banking, 2016)

Modeling the dyadic effects of parenting, stress, and coping on parent–child communication in families tested for hereditary breast-ovarian cancer risk - Jada G. Hamilton; Darren Mays; Tiffani DeMarco; Kenneth P. Tercyak (Familial Cancer, 2016)

Ecosystem Water-Use Efficiency of Annual Corn and Perennial Grasslands: Contributions from Land-Use History and Species Composition - Michael Abraha; Ilya Gelfand; Stephen K. Hamilton; Changliang Shao; Yahn-Jauh Su; G. Philip Robertson; Jiquan Chen (Ecosystems, 2016)

Guiding principles for the development and application of solid-phase phosphorus adsorbents for freshwater ecosystems - G. B. Douglas; D. P. Hamilton; M. S. Robb; G. Pan; B. M. Spears; M. Lurling (Aquatic Ecology, 2016)

Population‐level consequences for wild fish exposed to sublethal concentrations of chemicals – a critical review - Patrick B Hamilton; Ian G Cowx; Marjorie F Oleksiak; Andrew M Griffiths; Mats Grahn; Jamie R Stevens; Gary R Carvalho; Elizabeth Nicol; Charles R Tyler (Fish and Fisheries, 2016)
Concentrated chemical spills have been shown to impact adversely on fish populations and even cause localized population extinctions. Evaluating population‐level impacts of sublethal exposure concentrations is, however, complex and confounded by other environmental pressures. Applying effect measures derived from laboratory‐based chemical exposures to impacts in wild fish populations is constrained by uncertainty on how biochemical response measures (biomarkers) translate into health outcomes, lack of available data for chronic exposures and the many uncertainties in available fish population models. Furthermore, wild fish show phenotypic plasticity and local adaptations can occur that adds geographic and temporal variance on responses. Such population‐level factors are rarely considered in the chemical risk assessment process and can probably be derived only from studies on wild fish. Molecular technologies, including microsatellite and SNP genotyping, and RNAS eq for gene expression studies, are advancing our understanding of mechanisms of eco‐toxicological response, tolerance, adaptation and selection in wild populations. We examine critically the application of such approaches with examples including using microsatellites that has identified roach ( Rutilus rutilus ) populations living in rivers contaminated with sewage effluents that are self‐sustaining, and studies of stickleback ( Gasterosteus aculeatus ) and killifish ( Fundulus heteroclitus ) that have identified genomic regions under selection putatively related to pollution tolerance. Integrating data on biological effects between laboratory‐based studies and wild populations, and building understanding on adaptive responses to sublethal exposure are some of the priority research areas for more effective evaluation of population risks and resilience to contaminant exposure.

Within‐group relatedness is correlated with colony‐level social structure and reproductive sharing in a social fish - Jennifer K. Hellmann; Michael G. Sovic; H. Lisle Gibbs; Adam R. Reddon; Constance M. O'Connor; Isaac Y. Ligocki; Susan Marsh‐Rollo; Sigal Balshine; Ian M. Hamilton (Molecular Ecology, 2016)
In group‐living species, the degree of relatedness among group members often governs the extent of reproductive sharing, cooperation and conflict within a group. Kinship among group members can be shaped by the presence and location of neighbouring groups, as these provide dispersal or mating opportunities that can dilute kinship among current group members. Here, we assessed how within‐group relatedness varies with the density and position of neighbouring social groups in Neolamprologus pulcher , a colonial and group‐living cichlid fish. We used restriction site‐associated DNA sequencing ( RAD seq) methods to generate thousands of polymorphic SNP s. Relative to microsatellite data, RAD seq data provided much tighter confidence intervals around our relatedness estimates. These data allowed us to document novel patterns of relatedness in relation to colony‐level social structure. First, the density of neighbouring groups was negatively correlated with relatedness between subordinates and dominant females within a group, but no such patterns were observed between subordinates and dominant males. Second, subordinates at the colony edge were less related to dominant males in their group than subordinates in the colony centre, suggesting a shorter breeding tenure for dominant males at the colony edge. Finally, subordinates who were closely related to their same‐sex dominant were more likely to reproduce, supporting some restraint models of reproductive skew. Collectively, these results demonstrate that within‐group relatedness is influenced by the broader social context, and variation between groups in the degree of relatedness between dominants and subordinates can be explained by both patterns of reproductive sharing and the nature of the social landscape.

Reflectance properties of grey-scale Spectralon® as a function of viewing angle, wavelength, and polarization - A. Shaw; M. G. Daly; E. Cloutis; G. Basic; D. Hamilton; K. Tait; B. Hyde; E. Lymer; K. Balachandran (International Journal of Remote Sensing, 2016)

Interpolation study on ambient gamma levels in parts of Khasi Hills, Meghalaya (India): Preliminary findings for U exploration - B M KUKRETI; G K SHARMA; PRAMOD KUMAR; SANDEEP HAMILTON (Journal of Earth System Science, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Public Awareness of Direct-to-Consumer Genetic Tests: Findings from the 2013 U.S. Health Information National Trends Survey - Tanya Agurs-Collins; Rebecca Ferrer; Allison Ottenbacher; Erika A. Waters; Mary E. O’Connell; Jada G. Hamilton (Journal of Cancer Education, 2015)

Western Juniper Management: Assessing Strategies for Improving Greater Sage-grouse Habitat and Rangeland Productivity - Shahla Farzan; Derek J. N. Young; Allison G. Dedrick; Matthew Hamilton; Erik C. Porse; Peter S. Coates; Gabriel Sampson (Environmental Management, 2015)

Fermentation of Dilute Acid Pretreated Populus by Clostridium thermocellum, Caldicellulosiruptor bescii, and Caldicellulosiruptor obsidiansis - Kelsey L. Yee; Miguel Rodriguez; Choo Y. Hamilton; Scott D. Hamilton-Brehm; Olivia A. Thompson; James G. Elkins; Brian H. Davison; Jonathan R. Mielenz (BioEnergy Research, 2015)

The effect of long-term regional pumping on hydrochemistry and dissolved gas content in an undeveloped shale-gas-bearing aquifer in southwestern Ontario, Canada - Stewart M. Hamilton; Stephen E. Grasby; Jennifer C. McIntosh; Stephen G. Osborn (Hydrogeology Journal, 2015)

Empirical and semi-analytical chlorophyll a algorithms for multi-temporal monitoring of New Zealand lakes using Landsat - Mathew G. Allan; David P. Hamilton; Brendan Hicks; Lars Brabyn (Environmental Monitoring and Assessment, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Fish assemblage structure on sandy beaches with different anthropogenic influences and proximity of spawning grounds - Hamilton H Pereira; Leonardo M Neves; Marcus R da Costa; Francisco G Araújo (Marine Ecology, 2015)
Fish assemblages in an insular (preserved) and a continental (disturbed) sandy beach were compared to assess any changes that could be attributed to anthropogenic influences and/or the proximity of the fish spawning grounds. We expected that the closer geographical position to the spawning grounds and the small amount of anthropogenic disturbance on the insular beach would be likely to provide more suitable conditions for early fish development compared with the continental beach. A total of 192 samples (96 in each beach) were taken, yielding 68 fish species, mostly young‐of‐the‐year. Fish assemblage structure differed significantly between the two beaches. Moreover, the insular beach had higher number of species, number of individuals and biomass compared with the continental beach. The commercially important Clupeiformes Harengula clupeola, Anchoa tricolor and Anchoa januaria , Perciformes Micropogonias furnieri and Mugiliformes Mugil liza were typical species on the insular beach, partitioning the seasonal use of the beach. On the other hand, a few abundant non‐commercial species, mainly the Atheriniformes Atherinella brasiliensis and the Perciformes Eucinostomus argenteus and Diapterus rhombeus , occurred all year round at the continental beach. The high fish richness and abundance and the more conspicuous species turnover across seasons on the insular beach are probable indications of more complex and dynamic organization of the communities favored by better geographical position and less anthropogenic disturbance in the area.

Cross‐sectional study to investigate the presence of salmon pancreas disease virus in wild and feral fish populations in 10 lakes, L os L agos R egion, C hile - R Alegría; G Arriagada; S Urcelay; C Hamilton‐West (Journal of Fish Diseases, 2015)

Effects of a simulated upwelling event on the littoral epilithic diatom community of an ancient tropical lake (Lake Matano, Sulawesi Island, Indonesia) - Andrew J. Bramburger; Paul B. Hamilton; G. Douglas Haffner (Hydrobiologia, 2014)

Application of a Three-Dimensional Water Quality Model as a Decision Support Tool for the Management of Land-Use Changes in the Catchment of an Oligotrophic Lake - Dennis Trolle; Bob Spigel; David P. Hamilton; Ned Norton; Donna Sutherland; David Plew; Mathew G. Allan (Environmental Management, 2014)

Building local environmental knowledge in undergraduates with experiential wilderness skills and awareness training: the case of environmental sentinels - Jacob C. Brenner; Jason G. Hamilton; Tim Drake; Jed Jordan (Journal of Environmental Studies and Sciences, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Waterbird use of artificial wetlands in an Australian urban landscape - Christopher G. Murray; Sabine Kasel; Richard H. Loyn; Graham Hepworth; Andrew J. Hamilton (Hydrobiologia, 2013)

Crossability patterns within and among Oryza series Sativae species from Asia and Australia - Maria Celeste N. Banaticla-Hilario; Kenneth L. McNally; Ronald G. van den Berg; Nigel Ruaraidh Sackville Hamilton (Genetic Resources and Crop Evolution, 2013)

Central venous catheter-related blood stream infections in patients receiving intravenous iloprost for pulmonary hypertension - D. Sammut; C. A. Elliot; D. G. Kiely; I. J. Armstrong; L. Martin; J. Wilkinson; P. Sephton; J. Jones; N. Hamilton; J. Hurdman; E. McLellan; I. Sabroe; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

A Male-Predominant Cuticular Hydrocarbon, 7-Methyltricosane, is used as a Contact Pheromone in the Western Flower Thrips Frankliniella occidentalis - Oladele A. Olaniran; Akella V. S. Sudhakar; Falko P. Drijfhout; Ian A. N. Dublon; David R. Hall; James G. C. Hamilton; William D. J. Kirk (Journal of Chemical Ecology, 2013)

Reproductive biology of squaretail coralgrouper Plectropomus areolatus using age‐based techniques - K. L. Rhodes; B. M. Taylor; C. B. Wichilmel; E. Joseph; R. J. Hamilton; G. R. Almany (Journal of Fish Biology, 2013)
The squaretail coralgrouper Plectropomus areolatus was identified as a fast‐growing, early maturing and relatively short‐lived aggregation‐spawning epinephelid. Examinations of sectioned otoliths found females and males first maturing at 2 and 3 years, respectively, suggesting protogynous hermaphroditism; however, no transitionals were observed in samples. Age distribution for the two sexes was similar and both were represented in the oldest age class; however, significant sex‐specific differences in size‐at‐age were identified. Both sexes fully recruit into the fishery at age 4 years and reach 90% of asymptotic length by age 3 years. Underwater visual assessments, combined with the gonado‐somatic indices, revealed a 5 month reproductive season, with interannual variability observed in the month of highest density within the spawning aggregation. Catch restrictions on adults during spawning times and at reproductive sites, combined with gear‐based management and enhanced enforcement, are recommended to maintain spawning stocks. Based on the available evidence, the sexual pattern for this species is unresolved.

Thermodesulfobacterium geofontis sp. nov., a hyperthermophilic, sulfate-reducing bacterium isolated from Obsidian Pool, Yellowstone National Park - Scott D. Hamilton-Brehm; Robert A. Gibson; Stefan J. Green; Ellen C. Hopmans; Stefan Schouten; Marcel T. J. van der Meer; John P. Shields; Jaap S. S. Damsté; James G. Elkins (Extremophiles, 2013)

Estimating global arthropod species richness: refining probabilistic models using probability bounds analysis - Andrew J. Hamilton; Vojtech Novotný; Edward K. Waters; Yves Basset; Kurt K. Benke; Peter S. Grimbacher; Scott E. Miller; G. Allan Samuelson; George D. Weiblen; Jian D. L. Yen; Nigel E. Stork (Oecologia, 2013)

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

Physiological consequences of the supralittoral fringe: microhabitat temperature profiles and stress protein levels in the tropical periwinkle Cenchritis muricatus (Linneaus, 1758) - Michael L. Judge; Mark L. Botton; Mary G. Hamilton (Hydrobiologia, 2011)

Physiological responses of horseshoe crab (Limulus polyphemus) embryos to osmotic stress and a possible role for stress proteins (HSPs) - Morgan P. Greene; Mary G. Hamilton; Mark L. Botton (Marine Biology, 2011)

Landsat remote sensing of chlorophyll a concentrations in central North Island lakes of New Zealand - M. G. Allan; D. P. Hamilton; B. J. Hicks; L. Brabyn (International Journal of Remote Sensing, 2011)

Implications of global change for the maintenance of water quality and ecological integrity in the context of current water laws and environmental policies - Anna T. Hamilton; Michael T. Barbour; Britta G. Bierwagen (Hydrobiologia, 2010)

Research partnerships with local communities: two case studies from Papua New Guinea and Australia - G. R. Almany; R. J. Hamilton; D. H. Williamson; R. D. Evans; G. P. Jones; M. Matawai; T. Potuku; K. L. Rhodes; G. R. Russ; B. Sawynok (Coral Reefs, 2010)

Challenges and opportunities for integrating lake ecosystem modelling approaches - Wolf M. Mooij; Dennis Trolle; Erik Jeppesen; George Arhonditsis; Pavel V. Belolipetsky; Deonatus B. R. Chitamwebwa; Andrey G. Degermendzhy; Donald L. DeAngelis; Lisette N. De Senerpont Domis; Andrea S. Downing; J. Alex Elliott; Carlos Ruberto Fragoso; et al. (Aquatic Ecology, 2010)

IgE antibody-specific activity in human allergic disease - Robert G. Hamilton; Donald W. MacGlashan; Sarbjit S. Saini (Immunologic Research, 2010)

Ophiolite Tectonics, Rock Magnetism and Palaeomagnetism, Cyprus - G. J. Borradaile; F. Lagroix; T. D. Hamilton; D.-A. Trebilcock (Surveys in Geophysics, 2010)

Vertical distributions of chlorophyll in deep, warm monomictic lakes - David P. Hamilton; Katherine R. O’Brien; Michele A. Burford; Justin D. Brookes; Chris G. McBride (Aquatic Sciences, 2010)

Variants in toll-like receptors 2 and 9 influence susceptibility to pulmonary tuberculosis in Caucasians, African-Americans, and West Africans - Digna Rosa Velez; Christian Wejse; Martin E. Stryjewski; Eduardo Abbate; William F. Hulme; Jamie L. Myers; Rosa Estevan; Sara G. Patillo; Rikke Olesen; Alessandra Tacconelli; Giorgio Sirugo; John R. Gilbert; et al. (Human Genetics, 2010)

NOS2A, TLR4, and IFNGR1 interactions influence pulmonary tuberculosis susceptibility in African-Americans - Digna Rosa Velez; William F. Hulme; Jamie L. Myers; J. Brice Weinberg; Marc C. Levesque; Martin E. Stryjewski; Eduardo Abbate; Rosa Estevan; Sara G. Patillo; John R. Gilbert; Carol D. Hamilton; William K. Scott (Human Genetics, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Genetic variation in Eucalyptus nitens pulpwood and wood shrinkage traits - Matthew G. Hamilton; Carolyn A. Raymond; Chris E. Harwood; Brad M. Potts (Tree Genetics & Genomes, 2009)

Consequences of climate variability for the performance of bison in tallgrass prairie - JOSEPH M. CRAINE; E. GENE TOWNE; ANTHONY JOERN; ROBERT G. HAMILTON (Global Change Biology, 2009)
Climate variability is a major structuring factor in grassland ecosystems, yet there is great uncertainty in how changes in precipitation affect grazing herbivores. We determined how interannual variation in the timing and magnitude of precipitation affected the weight gain of free‐roaming bison in their first and second year. Bison weights were analyzed for 14 years for Konza Prairie, Kansas, and 12 years for Tallgrass Prairie Preserve, Oklahoma. Greater late‐summer precipitation increased bison weight gain. For every 100 mm precipitation, weight gain increased 6.4–15.3 kg depending on age classes and site. In contrast, greater midsummer precipitation decreased weight gain. For every additional 100 mm precipitation, weight decreased 9.7–17.3 kg depending on age class and site. The decreased weight gain of bison with greater midsummer precipitation was associated with increased grass stem production during the period for each of three dominant grasses at Konza Prairie. Although greater stem production increases the quantity of aboveground biomass, it should decrease the overall nutritional quality of biomass to grazers, which would reduce weight gain. With offsetting effects of mid‐ and late‐summer precipitation on weight gain, these results show that predicting the effects of climate change on grazers must incorporate both the timing and magnitude of changes in precipitation and their effects on both the quantity and quality of biomass.

The plankton community of Lake Matano: factors regulating plankton composition and relative abundance in an ancient, tropical lake of Indonesia - Elisabeth Sabo; Denis Roy; Paul B. Hamilton; Peter E. Hehanussa; Roger McNeely; G. Douglas Haffner (Hydrobiologia, 2008)

Processes regulating the community composition and relative abundance of taxa in the diatom communities of the Malili Lakes, Sulawesi Island, Indonesia - Andrew J. Bramburger; Paul B. Hamilton; Peter E. Hehanussa; G. Douglas Haffner (Hydrobiologia, 2008)

QBO influence on extratropical predictive skill - G. J. Boer; K. Hamilton (Climate Dynamics, 2008)

Effective population size dynamics reveal impacts of historic climatic events and recent anthropogenic pressure in African elephants - J. B. A. OKELLO; G. WITTEMYER; H. B. RASMUSSEN; P. ARCTANDER; S. NYAKAANA; I. DOUGLAS‐HAMILTON; H. R. SIEGISMUND (Molecular Ecology, 2008)
Two hundred years of elephant hunting for ivory, peaking in 1970–1980s, caused local extirpations and massive population declines across Africa. The resulting genetic impacts on surviving populations have not been studied, despite the importance of understanding the evolutionary repercussions of such human‐mediated events on this keystone species. Using Bayesian coalescent‐based genetic methods to evaluate time‐specific changes in effective population size, we analysed genetic variation in 20 highly polymorphic microsatellite loci from 400 elephants inhabiting the greater Samburu‐Laikipia region of northern Kenya. This area experienced a decline of between 80% and 90% in the last few decades when ivory harvesting was rampant. The most significant change in effective population size, however, occurred approximately 2500 years ago during a mid–Holocene period of climatic drying in tropical Africa. Contrary to expectations, detailed analyses of four contemporary age‐based cohorts showed that the peak poaching epidemic in the 1970s caused detectable temporary genetic impacts, with genetic diversity rebounding as juveniles surviving the poaching era became reproductively mature. This study demonstrates the importance of climatic history in shaping the distribution and genetic history of a keystone species and highlights the utility of coalescent‐based demographic approaches in unravelling ancestral demographic events despite a lack of ancient samples. Unique insights into the genetic signature of mid‐Holocene climatic change in Africa and effects of recent poaching pressure on elephants are discussed.

Social dominance, seasonal movements, and spatial segregation in African elephants: a contribution to conservation behavior - G. Wittemyer; W. M. Getz; F. Vollrath; I. Douglas-Hamilton (Behavioral Ecology and Sociobiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Population genetic consequences of geographic disjunction: a prairie plant isolated on Great Lakes alvars - J. A. HAMILTON; C. G. ECKERT (Molecular Ecology, 2007)
Species may often exhibit geographic variation in population genetic structure due to contemporary and historical variation in population size and gene flow. Here, we test the predictions that populations on the margins of a species’ distribution contain less genetic variation and are more differentiated than populations towards the core of the range by comparing patterns of genetic variation at five microsatellite loci between disjunct and core populations of the perennial, allohexaploid herb Geum triflorum . We sampled nine populations isolated on alvar habitat within the eastern Great Lakes region in North America, habitats that include disjunct populations of several plant species, and compared these to 16 populations sampled from prairie habitat throughout the core of the species’ distribution in midwestern Canada and the USA. Alvar populations exhibited much lower within‐population diversity and contained only a subset of alleles found in prairie populations. We detected isolation by distance across the species’ range and within alvar and prairie regions separately. As predicted, genetic differentiation was higher among alvar populations than among prairie populations, even after controlling for the geographic distance between sampled populations. Low diversity and high differentiation can be accounted for by the greater contemporary spatial isolation of alvar populations. However, the genetic structure of alvar populations may also have been influenced by postglacial range expansion and contraction. Our results are consistent with alvar populations being founded during an expansion of prairie habitat during the warmer, hypsithermal period ∼5000 bp and subsequently becoming stranded on isolated alvar habitat as the climate grew cooler and wetter.

Inferring climate sensitivity from volcanic events - G. J. Boer; M. Stowasser; K. Hamilton (Climate Dynamics, 2007)

Resource‐based adaptive divergence in the freshwater fish Telmatherina from Lake Matano, Indonesia - DENIS ROY; GORD PATERSON; PAUL B. HAMILTON; DANIEL D. HEATH; G. DOUGLAS HAFFNER (Molecular Ecology, 2007)
Adaptive radiations are an important source of biodiversity, but resolving which ecological pressures seed these processes in natural systems remains difficult. Here the adaptive radiation among Telmatherina , a genus of freshwater fish endemic to an ancient lake in central Sulawesi, Indonesia, was examined to determine its causal root. We demonstrate that all Telmatherina in this lake can be categorized into three lineages each possessing specialized skull shapes and pharyngeal jaw bones allowing them to exploit different resources. These data demonstrate a natural example of how resource partitioning has likely initiated adaptive radiation in a resource limited environment.

Shorebirds, snails, and the amphipod (Corophium volutator) in the upper Bay of Fundy: top–down vs. bottom–up factors, and the influence of compensatory interactions on mudflat ecology - Diana J. Hamilton; Antony W. Diamond; Peter G. Wells (Hydrobiologia, 2006)

Empirical indices of spatial and executive processes in visuo-spatial working memory - J. M. Thompson; C. J. Hamilton; J. M. Gray; J. G. Quinn; P. Mackin; I. N. Ferrier; A. H. Young (Cognitive Processing, 2006)

Comparison of photosynthetic damage from arthropod herbivory and pathogen infection in understory hardwood saplings - Mihai Aldea; Jason G. Hamilton; Joseph P. Resti; Arthur R. Zangerl; May R. Berenbaum; Thomas D. Frank; Evan H. DeLucia (Oecologia, 2006)

Annual basal area increment and growth duration of Pinus taeda in response to eight years of free‐air carbon dioxide enrichment - DAVID J. P. MOORE; SUSANNE AREF; RINGO M. HO; JEFFREY S. PIPPEN; JASON G. HAMILTON; EVAN H. DE LUCIA (Global Change Biology, 2006)
Rising CO 2 is predicted to increase forest productivity, although the duration of the response and how it might be altered by variation in rainfall, temperature and other environmental variables are not well understood. We measured the basal area of rapidly growing Pinus taeda trees exposed to free‐air CO 2 enrichment for 8 years and used these measurements to estimate monthly and annual growth. We used these measurements in a statistical model to estimate the start and end of growth in each year. Elevated CO 2 increased the basal area increment ( BAI ) of trees by 13–27%. In most years, exposure to elevated CO 2 increased the growth rate but not the duration of the active growth period. With the exception of 1 year following an extreme drought and a severe ice storm, BAI was positively correlated with the amount of rainfall during the active growth period. The interannual variation in the relative enhancement of BAI caused by elevated CO 2 was strongly related to temperature and rainfall, and was greatest in years with high vapor pressure deficit. There was no evidence of a systematic reduction in the stimulation of growth during the first 8 years of this experiment, suggesting that the hypothesized limitation of the CO 2 response caused by nitrogen availability has yet to occur.

Geographical Clustering of Pancreatic Cancers in the Northeast Nile Delta Region of Egypt - A. S. Soliman; X. Wang; J.-D. Stanley; N. El-Ghawalby; M. L. Bondy; F. Ezzat; A. Soultan; M. Abdel-Wahab; O. Fathy; G. Ebidi; N. Abdel-Karim; K.-Anh. Do; et al. (Archives of Environmental Contamination and Toxicology, 2006)

Hinge peptide combinatorial libraries for inhilbitors of botulinum neurotoxins and saxitoxin: Deconvolution strategy - Graham J. Moore; Diana M. Moore; Samir S. Roy; Lawrence J. Hayden; Murray G. Hamilton; Nora W. C. Chan; William E. Lee (Molecular Diversity, 2006)

Mapping autosomal dominant progressive limb-girdle myopathy with bone fragility to chromosome 9p21-p22: a novel locus for a musculoskeletal syndrome - Giles D.J. Watts; Sarju G. Mehta; Chengfeng Zhao; Sheena Ramdeen; Sara Jane Hamilton; Deborah V. Novack; Steven Mumm; Michael P. Whyte; Barbara Mc Gillivray; Virginia E. Kimonis (Human Genetics, 2005)

Identification of a Male-produced Aggregation Pheromone in the Western Flower Thrips Frankliniella occidentalis - James G. C. Hamilton; David R. Hall; William D. J. Kirk (Journal of Chemical Ecology, 2005)

Climate sensitivity and climate change under strong forcing - G. J. Boer; K. Hamilton; W. Zhu (Climate Dynamics, 2005)

Insect herbivory in an intact forest understory under experimental CO 2 enrichment - May R. Berenbaum; Jeffrey Pippen; Mihai Aldea; Evan H. DeLucia; Jason G. Hamilton; Arthur R. Zangerl (Oecologia, 2004)

Letters - Scott Kiewit; Richard G. Reid; Lawrence S. Hamilton (Journal of Forestry, 2004)

Evidence for a Male-Produced Sex Pheromone in the Western Flower Thrips Frankliniella occidentalis - William D. J. Kirk; James G. C. Hamilton (Journal of Chemical Ecology, 2004)

Hydrologic description of forested wetlands in northeastern New Jersey, USA—An urban/suburban region - Joan G. Ehrenfeld; Heather Bowman Cutway; Robert Hamilton; Emilie Stander (Wetlands, 2003)

Recent occurrence of Cylindrospermopsis raciborskii in Waikato lakes of New Zealand - E. F. Ryan; D. P. Hamilton; G. E. Barnes (New Zealand Journal of Marine and Freshwater Research, 2003)
Cylindrospermopsis raciborskii is a toxin‐producing species of cyanobacteria that in autumn 2003 was recorded for the first time in three shallow (max. depth ≤5 m) Waikato lakes and a hydro‐electric dam on the Waikato River, New Zealand. It formed water blooms at densities >100 000 cells/ml in Lakes Waahi and Whangape. Net rates of population growth >0.2 day –1 were recorded for C. raciborskii in Lakes Ngaroto, Waahi, and Karapiro, based on comparisons of low numbers (detection of 15 000 cells/ml) in the subsequent sample “x”‐“y” days later. C. raciborskii may be well adapted to rapid proliferation in the Waikato lakes, which are eutrophic to hypertrophic, with high light attenuation, and where nitrogen (N) fixation may provide it with a competitive advantage over non‐nitrogen fixing algae under N‐limited conditions.

Analysis of Anal Droplets of the Western Flower Thrips Frankliniella occidentalis - Kenneth M. MacDonald; James G. C. Hamilton; Robert Jacobson; William D. J. Kirk (Journal of Chemical Ecology, 2003)

Genetic identification of two sibling species of Lutzomyia longipalpis (Diptera: Psychodidae) that produce distinct male sex pheromones in Sobral, Ceará State, Brazil - R. D. C. Maingon; R. D. Ward; J. G. C. Hamilton; H. A. Noyes; N. Souza; S. J. Kemp; P. C. Watts (Molecular Ecology, 2003)
Lutzomyia longipalpis , the main sandfly vector for New World visceral leishmaniasis is a complex of an as yet undefined number of sibling species. At present, there is no consensus on the status (single species vs. species complex) of Brazilian populations. We applied five microsatellite loci to test the hypothesis that L. longipalpis occurs as two sympatric cryptic species in Sobral, Ceará State, Brazil as predicted by male sex pheromone chemotypes described previously for field specimens from this site [ S‐ 9‐methyl‐germacrene‐B ( 9MGB) and a cembrene compound]. Abdominal spot morphology corresponds with pheromone type at this locality (9MGB in ‘1 spot’ males and cembrene in ‘2 spot’ males). Genotype data from 190 wild‐caught L. longipalpis specimens collected in October 1999 and April 2001 were used to estimate genetic differentiation between the two sex pheromone populations and sampling dates. No significant ( P > 0.05) genetic differences were found between the 1999 and 2001 9MGB samples (θ = 0.018; R ST = −0 . 005), and genetic differentiation was low between the cembrene collections (θ = 0.037, P R ST = −0.043, P > 0.05). By contrast, highly divergent allelic frequencies (largely at two microsatellite loci) corresponded to significant ( P > 0.05) genetic differentiation (θ = 0.221; R ST = 0.215) for all comparisons between samples with different pheromones. When pheromone samples were pooled across sample date, genetic differentiation was high (θ = 0.229; P N e m = 0.84). The allele frequency distribution at each of the five microsatellite loci was similar for males and females from the two collection years. Two of these loci showed highly divergent allele frequencies in the two sex pheromone populations. This was reflected in the highly significant genetic differentiation obtained from the male genotypes, between populations producing different pheromones (θ = 0.229–0.268; P P L. longipalpis .

Changes in Brain Intracellular pH and Membrane Phospholipids on Oxygen Therapy in Hypoxic Patients with Chronic Obstructive Pulmonary Disease - G. Hamilton; R. Mathur; J.M. Allsop; D.M. Forton; N.S. Dhanjal; R.J. Shaw; S.D. Taylor-Robinson (Metabolic Brain Disease, 2003)

The nitrogen budget of a pine forest under free air CO2 enrichment - Adrien C. Finzi; Evan H. DeLucia; Jason G. Hamilton; Daniel D. Richter; William H. Schlesinger (Oecologia, 2002)

Forest carbon balance under elevated CO2 - Jason G. Hamilton; Evan H. DeLucia; Kate George; Shawna L. Naidu; Adrien C. Finzi; William H. Schlesinger (Oecologia, 2002)

Cellular engineering of vascular bypass grafts: Role of chemical coatings for enhancing endothelial cell attachment - H. J. Salacinski; A. Tiwari; G. Hamilton; A. M. Seifalian (Medical & Biological Engineering & Computing, 2001)

Pollen‐based biome reconstruction for southern Europe and Africa 18,000 yr bp - H. Elenga; O. Peyron; R. Bonnefille; D. Jolly; R. Cheddadi; J. Guiot; V. Andrieu; S. Bottema; G. Buchet; J.‐L. De Beaulieu; A. C. Hamilton; J. Maley; et al. (Journal of Biogeography, 2000)
Pollen data from 18,000 14 C yr bp were compiled in order to reconstruct biome distributions at the last glacial maximum in southern Europe and Africa. Biome reconstructions were made using the objective biomization method applied to pollen counts using a complete list of dryland taxa wherever possible. Consistent and major differences from present‐day biomes are shown. Forest and xerophytic woods/scrub were replaced by steppe, both in the Mediterranean region and in southern Africa, except in south‐western Cape Province where fynbos (xerophytic scrub) persisted. Sites in the tropical highlands, characterized today by evergreen forest, were dominated by steppe and/or xerophytic vegetation (cf. today’s Ericaceous belt and Afroalpine grassland) at the last glacial maximum. Available data from the tropical lowlands are sparse but suggest that the modern tropical rain forest was largely replaced by tropical seasonal forest while the modern seasonal or dry forests were encroached on by savanna or steppe. Montane forest elements descended to lower elevations than today.

The red alga Asparagopsis taxiformis\Falkenbergia hillebrandii–a possible source of trichloroethylene and perchloroethylene? - Rhoda A. Marshall; John T. G. Hamilton; Matthew J. Dring; David B. Harper (Limnology and Oceanography, 2000)

Initial in vitro characterisation of phosphonopyruvate hydrolase, a novel phosphate starvation-independent, carbon-phosphorus bond cleavage enzyme in Burkholderia cepacia Pal6 - N. G. Ternan; J. T. G. Hamilton; J. P. Quinn (Archives of Microbiology, 2000)

Expressed sequence tags derived from brain tissue of Oreochromis niloticus - L. C. Hamilton; G. R. Macpherson; J. M. Wright (Journal of Fish Biology, 2000)
Expressed sequence tags (ESTs) were obtained from complementary DNA libraries derived from the brain of the cichlid fish, Oreochromis niloticus. Single‐pass sequencing of 183 cDNA clones generated 294 ESTs; 57 of these clones (31%) were identified based on their similarity to sequences in GenBank.

Coexistence and interference between a native perennial grass and non-native annual grasses in California - J. G. Hamilton; Claus Holzapfel; Bruce E. Mahall (Oecologia, 1999)

The biosynthetic relationship between littorine and hyoscyamine in transformed roots of Datura stramonium - I. Zabetakis; R. Edwards; John T. G. Hamilton; D. O'Hagan (Plant Cell Reports, 1998)

Ion channels in isolated mouse jejunal crypts - A. G. Butt; K. L. Hamilton (Pflügers Archiv - European Journal of Physiology, 1998)

Spatial variability of soil total C and N and their stable isotopes in an upland Scottish grassland - C.A. Marriott; G. Hudson; D. Hamilton; R. Neilson; B. Boag; L.L. Handley; J. Wishart; C.M. Scrimgeour; D. Robinson (Plant and Soil, 1997)

The release of genetically modified grasses. Part 1: pollen dispersal to traps in Lolium perenne - G. D. Giddings; N. R. Sackville Hamilton; M. D. Hayward (Theoretical and Applied Genetics, 1997)

The release of genetically modified grasses. Part 2: the influence of wind direction on pollen dispersal - G. D. Giddings; N. R. Sackville Hamilton; M. D. Hayward (Theoretical and Applied Genetics, 1997)

The third human isoform of 6-phosphofructo-2-kinasefructose-2,6-bisphosphatase (PFKFB3) Map position 10p14–p15 - J. Nicholl; J. A. Hamilton; G. R. Sutherland; R.L. Sutherland; C. K. W. Watts (Chromosome Research, 1997)

Characterization, scaling, and partial representation of diffuse and discrete input junctions to CA3 hippocampus - F. G. Ascarrunz; M. A. Kisley; K. A. Flach; R. W. Hamilton; R. J. MacGregor (Biological Cybernetics, 1995)

Characterization, scaling, and partial representation of diffuse and discrete input junctions to CA3 hippocampus - F. G. Ascarrunz; M. A. Kisley; K. A. Flach; R. W. Hamilton; R. J. MacGregor (Biological Cybernetics, 1995)

Distribution of the bispyridinium oxime [14C] HI-6 in male and female rats - Paul M. Lundy; Brian T. Hand; Brian R. Broxup; George Yipchuck; Murray G. Hamilton (Archives of Toxicology, 1990)

Strontium in rivers of the Baltic Basin - Runo Lfvendahl; Gran berg; P. Joseph Hamilton (Aquatic Sciences, 1990)

Skeletal deformities in smallmouth bass,Micropterus dolomieui, from southern Appalachian reservoirs - M. J. Van Den Avyle; S. J. Garvick; V. S. Blazer; S. J. Hamilton; W. G. Brumbaugh (Archives of Environmental Contamination and Toxicology, 1989)

HI-6 therapy of soman and tabun poisoning in primates and rodents - Murray G. Hamilton; Paul M. Lundy (Archives of Toxicology, 1989)

The rate of turnover of the adenosine triphosphate pool of Escherichia coli growing aerobically in simple defined media - W. H. Holms; I. D. Hamilton; A. G. Robertson (Archives of Microbiology, 1972)